Watch What I Do, Not What I Say: The Unintended Consequences of the Homeland Investment Act - DHARMAPALA, DHAMMIKA; FOLEY, C. FRITZ; FORBES, KRISTIN J. (Journal of Finance, 2011)
ABSTRACT The Homeland Investment Act provided a tax holiday for the repatriation of foreign earnings. Advocates argued the Act would alleviate financial constraints by reducing the cost to U.S. multinationals of accessing internal capital. This paper shows that repatriations did not increase domestic investment, employment, or R&D—even for firms that appeared to be financially constrained or lobbied for the holiday. Instead, a $1 increase in repatriations was associated with a $0.60 to $0.92 increase in shareholder payouts. Regulations intended to restrict such payouts were undermined by the fungibility of money. Results indicate that U.S. multinationals were not financially constrained and were well‐governed.